2016
DOI: 10.15171/ijhpm.2016.117
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Implementation of the Health and Rehabilitation Articles of the United Nations Convention on the Rights of Persons with Disabilities in South Africa

Abstract: Background: The United Nations (UN) Convention on the Rights of Persons with Disabilities (CRPD) is a milestone in the recognition of the human rights of persons with disabilities, including the right to health and rehabilitation. South Africa has signed and ratified the CRPD but still has a long way to go in reforming policies and systems in order to be in compliance with the convention. This paper seeks to fill a gap in the literature by exploring what the barriers to the implementation of the health and reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
5
40
0
1
Order By: Relevance
“…Despite this legislation, participants in this study identified potential discrimination against persons with developmental disabilities as the result of employer-based stigma, especially if an employer has past negative experience in employing a person with developmental disabilities. The same has been reported elsewhere where stigma and negative assumptions about persons with disabilities were seen as key barriers to implementation of rights-based policies such as the United Nations Convention on the Rights of Persons with Disabilities [90]. The fact that stigma was one of the top three barriers to participation or sustaining participation in the labour market for persons with developmental disabilities suggests that despite significant constitutional and institutional support and protection, persons with developmental disabilities continue to face extensive and deleterious discrimination.…”
Section: Discussionsupporting
confidence: 65%
“…Despite this legislation, participants in this study identified potential discrimination against persons with developmental disabilities as the result of employer-based stigma, especially if an employer has past negative experience in employing a person with developmental disabilities. The same has been reported elsewhere where stigma and negative assumptions about persons with disabilities were seen as key barriers to implementation of rights-based policies such as the United Nations Convention on the Rights of Persons with Disabilities [90]. The fact that stigma was one of the top three barriers to participation or sustaining participation in the labour market for persons with developmental disabilities suggests that despite significant constitutional and institutional support and protection, persons with developmental disabilities continue to face extensive and deleterious discrimination.…”
Section: Discussionsupporting
confidence: 65%
“…One belief system that appeared to discourage people with disabilities and their caregivers from seeking any healthcare services, including primary healthcare, was the belief that disability is related to or caused by higher powers outside of the person, such as religion or witchcraft [38][39][40][41][42]. This belief was often interpreted as the disability or any other symptoms experienced by an individual with a disability being inflicted by an external power, resulting in feelings that there was no point in seeking healthcare intervention and so treatments were only sought from traditional healers who might free the person of the condition [38][39][40][41][42]. While this belief was mostly expressed by people with disabilities and their caregivers in the studies, it is possible that it may have also been the driving force in many of the negative interactions experienced by people with disabilities and their caregivers from community members and healthcare stakeholders, who may have shared these beliefs.…”
Section: Cultural Beliefs and Attitudinal Barriersmentioning
confidence: 99%
“…Both documents put emphasis on the importance of available and affordable assistive technology for persons with disabilities [32]. Yet other research in South Africa suggests that the failure to effectively implement the health and rehabilitation articles of the UNCRPD is largely due not only to negative attitudes in society in general [32] but also from government officials and service providers towards people with disabilities [33] and a rights-based approach. This certainly incorporates most people who use assistive products.…”
Section: Policy In Low-and Middle-income Countriesmentioning
confidence: 99%